Events that shape genomes - Schlebusch, Stephen A. (Department of Molecular and Cell Biology, 2020)
The invention and development of Next Generation Sequencing has opened up new possibilities for exploring the genomes of non-model organisms. For this thesis, a diverse range of non-model species from both plants and animals were used to identify and answer questions of evolutionary interest in four case studies. In doing so, a wide assortment of methodologies were used and developed, taking full advantage of the versatility that whole genome sequencing can provide. The genome of the Natal Long Fingered Bat, Miniopterus natalensis, was assembled to investigate the genetic mechanisms responsible for the evolution of the bat wing. The assembled genome was required to facilitate RNA-seq and ChIP-seq analysis. In addition to the genome assembly and annotation, dN/dS analysis and lncRNA prediction were also conducted. This resulted in a high quality genome assembly with just over 24000 genes being annotated and 227 putative lncRNAs being identified. None of the genetic pathways highlighted by the RNA-seq analysis showed any elevated dN/dS signal, suggesting this was not the loci of evolutionary change. The Amboseli National Park in Kenya has a local population of Yellow baboons (Papio cynocephalus) that has recently come into contact and hybridised with a population of Olive baboons (Papio anubis). A genome assembly of P. cynocephalus was created and used to align low coverage sequencing from 45 baboons, including admixed individuals along with unadmixed individuals from each species. By identifying SNPs that were predictive of the species, hybrid individuals were confirmed and evidence for previous admixture events discovered, such as P. anubis SNPs already at fixation in the P. cynocephalus population at Amboseli. The Ruschioideae are a clade of plants that encompasses the prolific tribe, the Ruschieae, which is comprised of approximately 1500 recently diverged species. An exploratory analysis sequenced two Ruschieae genomes (Polymita steenbokensis and Faucaria felina) along with a sister taxon (Cleretum herrei) from a neighbouring tribe (Dorotheantheae). The three plants were compared to each other in order to try and identify any genetic signatures that could be influencing the rapid speciation. The two Ruschieae species were found to have increased levels of non-tandem duplication within the genome as well as on going transposable element activity when compared to C. herrei. Xerohpyta humilis is a desiccation tolerant plant. In order to further facilitate research into how this is possible, the genome was sequenced and assembled. Irregular data led to the discovery that the plant had a genome duplication as well as a large amount of somatic mutations in its genome. Further analysis confirmed that this pattern of somatic mutations was only present in plants that had undergone multiple cycles of desiccation and rehydration. These apparently disparate topics explored the possibilities and limitations for whole genome sequencing in the study of non-model organisms. Mechanisms of genetic change were examined at the genomic scale, from adaptation and hybridisation to various forms of duplication and mutation. In this way, a large variety of events responsible for the evolutionary change of genomes in plants and animals were analysed in a diverse set of systems.